Prevention of Virus Persistence and Protection against Immunopathology after Borna Disease Virus Infection of the Brain by a Novel Orf Virus Recombinant - Henkel, Marco (American Society for Microbiology, 2005)
The Parapoxvirus Orf virus represents a promising candidate for novel vector vaccines due to its immune modulating properties even in nonpermissive hosts such as mouse or rat. The highly attenuated Orf virus strain D1701 was used to generate a recombinant virus (D1701-VrVp40) expressing nucleoprotein p40 of Borna disease virus, which represents a major antigen for the induction of a Borna disease virus-specific humoral and cellular immune response. Infection with Borna disease virus leads to distinct neurological symptoms mediated by the invasion of activated specific CD8(+) T cells into the infected brain. Usually, Borna disease virus is not cleared from the brain but rather persists in neural cells. In the present study we show for the first time that intramuscular application of the D1701-VrVp40 recombinant protected rats against Borna disease, and importantly, virus clearance from the infected brain was demonstrated in immunized animals. Even 4 and 8 months after the last immunization, all immunized animals were still protected against the disease. Initial characterization of the immune cells attracted to the infected brain areas suggested that D1701-VrVp40 mediated induction of B cells and antibody-producing plasma cells as well as T cells. These findings suggest the induction of various defense mechanisms against Borna disease virus. First studies on the role of antiviral cytokines indicated that D1701-VrVp40 immunization did not lead to an enhanced early response of gamma or alpha interferon or tumor necrosis factor alpha. Collectively, this study describes the potential of the Orf virus vector system in mediating long-lasting, protective antiviral immunity and eliminating this persistent virus infection without provoking massive neuronal damage.